Deconstructing the Kiai and Santri Relationship: A Critical Review of Power and Cultural Dynamics - Balya Ziaulhaq Achmadin; Mohammad Asrori; Ahmad Barizi; Abdul Malik Karim Amrullah; Muhammad Muntahibun Nafis (El Harakah)
This study aims to reveal the dynamics of the relationship between Kiai and santri in traditional pesantren. This research deconstructs the relationship between Kiai and Santri in the Indonesian socio-cultural context. Through a critical approach, this study examines the dynamics of power and cultural influences that color the relationship. By analyzing various sources, this study reveals the complexity of the Kiai and Santri relationship that goes beyond the traditional teacher-student relationship. The results show that the relationship between Kiai and santri in traditional pesantren is built on the basis of strong religious and cultural values. Kiai holds a central role as a spiritual leader and teacher, while santri place themselves as obedient and respectful students. This relationship is characterized by a clear hierarchy, where Kiai has great authority and influence over santri. However, the dynamics of this relationship do not always run smoothly. There are potential conflicts that arise due to differences in interpretation of religious values, differences in socio-economic backgrounds, and the influence of changing times. Kiai are required to be able to maintain a balance between maintaining traditional values and adjusting to the demands of the times and their relevance to social and political changes affecting the relationship between Kiai and Santri